2017
DOI: 10.1128/jb.00011-17
|View full text |Cite
|
Sign up to set email alerts
|

Light Modulates Metabolic Pathways and Other Novel Physiological Traits in the Human Pathogen Acinetobacter baumannii

Abstract: Light sensing in chemotrophic bacteria has been relatively recently ascertained. In the human pathogen Acinetobacter baumannii, light modulates motility, biofilm formation, and virulence through the blue-light-sensing-using flavin (BLUF) photoreceptor BlsA. In addition, light can induce a reduction in susceptibility to certain antibiotics, such as minocycline and tigecycline, in a photoreceptorindependent manner. In this work, we identified new traits whose expression levels are modulated by light in this path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 49 publications
2
67
0
Order By: Relevance
“…Up to 0.5 µmol trehalose/mg of protein were detected, but the differences may also be due to different extraction/detection procedures. Another interesting observation concerning trehalose biosynthesis in A. baumannii has been published very recently: expression of otsBA (and other genes) was shown to be modulated by light (Müller et al ., ). In A. baumannii ATCC 19606 wild type, 10 µmol trehalose/g dry weight (which equals ca.…”
Section: Discussionmentioning
confidence: 97%
“…Up to 0.5 µmol trehalose/mg of protein were detected, but the differences may also be due to different extraction/detection procedures. Another interesting observation concerning trehalose biosynthesis in A. baumannii has been published very recently: expression of otsBA (and other genes) was shown to be modulated by light (Müller et al ., ). In A. baumannii ATCC 19606 wild type, 10 µmol trehalose/g dry weight (which equals ca.…”
Section: Discussionmentioning
confidence: 97%
“…Whether the trehalose biosynthesis enzymes OtsA and OtsB are osmotically regulated as well, as in E. coli (Giæver et al ., ), remains to be established, but a transcriptional activation by the osmolarity of the environment was demonstrated (Zeidler et al ., ). Furthermore, high temperature as well as blue light stimulated transcription of otsBA and trehalose accumulation independent of high osmolarity (Müller et al ., ; Zeidler et al ., ). In contrast to the mtlD promoter, no suppression by other compatible solutes was found for the otsBA promoter, which can be explained by a role of trehalose in other stress responses and points towards a different mechanism of regulation (Zeidler et al ., ).…”
Section: How Can Acinetobacter Baumannii Adapt To High Osmolarities?mentioning
confidence: 99%
“…Recently, several in-vitro studies have shown that A. baumannii can respond to extracellular stimuli such as bile salts, mucin, light, antibiotics and human serum, among others, modifying the expression of genes involved in biofilm formation, degradation of phenylacetic acid, metabolic pathways, and genes coding for the Type VI secretion system (T6SS) [10,11]. In addition, in-vivo studies performed with a life-threatening bacteremia animal model using A. baumannii ATCC 17878-infected mice showed up-regulation of genes associated with three iron uptake systems, whereas genes related to metabolism, quorum sensing, and biofilm formation were down-regulated, highlighting the ability of A. baumannii to adapt to fluctuating environments [12].…”
Section: Introductionmentioning
confidence: 99%